Some Issues with Higher Education in Africa - Cole, Lawalley (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
This policy paper highlights several macro issues with African higher education, including inadequate funding, governance challenges, and a lack of access to digital infrastructure compounded by the COVID-19 pandemic. The paper also notes the historical and continuing impact of colonialism on Africa’s education systems and women’s challenges in accessing higher education. The author emphasizes the importance of investing in human capital and improving the quality of primary education to strengthen Africa’s human resource base and advance economic development. The paper calls for a paradigm shift in education policy and practice, underscoring pragmatism over ideology and focusing on building the capacity for sustained development through training in science, engineering, medicine, and agriculture. The author also highlights the need to address gender inequalities in access to higher education and diversify institutional models to meet the demands of the digital age. Ultimately, the paper calls for a concerted effort to improve funding, governance, and quality across African higher education institutions, leveraging partnerships and innovations to expand access and promote excellence.